Strategi Fleksibiliti dan Performansi Perusahaan UMKM Suatu Kajian Konseptual - Thamrin Husen (Program Studi Magister Manajemen, 2013)
Today knowledge age firms operate in more turbulent business and market dynamic environments, managers need to take proactive in creating to combating strategies for such environments and to adapt to such external turbulent environments. Incorporation of ‘Flexibility’ in strategic of any organization becomes very important in all the perspectives of the business organization. Although in the current market dynamic environment, firms looking for sustainable growth in their business performance need to be strategic flexible in their business operations. This paper few conceptual studies have examined the coorelation of strategic flexibility on business performance Small Medium Entreprises (SME). This paper presents the result of a study that was designed to identify if strategic flexibility will be related to business performance SMEs in Sumatera Barat. This paper also emphasizes on how flexibility has evolved as a concept and taken a shape of strategic driver to improve firm performance. Keywords: strategic flexibility, firm performance